Rapamycin increases survival in ALS mice lacking mature lymphocytes - Staats, Kim A (BioMed Central, 2013)
BACKGROUND: Amyotrophic Lateral Sclerosis (ALS) is a devastating progressive neurodegenerative disease. Disease pathophysiology is complex and not yet fully understood, but is proposed to include the accumulation of misfolded proteins, as aggregates are present in spinal cords from ALS patients and in ALS model organisms. Increasing autophagy is hypothesized to be protective in ALS as it removes these aggregates. Rapamycin is frequently used to increase autophagy, but is also a potent immune suppressor. To properly assess the role of rapamycin-induced autophagy, the immune suppressive role of rapamycin should be negated. FINDINGS: Autophagy is increased in the spinal cord of ALS mice. Dietary supplementation of rapamycin increases autophagy, but does not increase the survival of mutant SOD1 mice. To measure the effect of rapamycin in ALS independent of immunosuppression, we tested the effect of rapamycin in ALS mice deficient of mature lymphocytes. Our results show that rapamycin moderately increases the survival of these ALS mice deficient of mature lymphocytes. CONCLUSIONS: Rapamycin could suppress protective immune responses while enhancing protective autophagy reactions during the ALS disease process. While these opposing effects can cancel each other out, the use of immunodeficient mice allows segregation of effects. Our results indicate that maximal therapeutic benefit may be achieved through the use of compounds that enhance autophagy without causing immune suppression.